THE GOODNESS OF SIMULTANEOUS FITS IN ISIS - Matthias Kühnel; Sebastian Falkner; Christoph Grossberger; Ralf Ballhausen; Thomas Dauser; Fritz-Walter Schwarm; Ingo Kreykenbohm; Michael A. Nowak; Katja Pottschmidt; Carlo Ferrigno; Richard E. Rothschild; Silvia Martínez-Núñez; et al. (Acta Polytechnica, 2016)
In a previous work, we introduced a tool for analyzing multiple datasets simultaneously, which has been implemented into ISIS. This tool was used to fit many spectra of X-ray binaries. However, the large number of degrees of freedom and individual datasets raise an issue about a good measure for a simultaneous fit quality. We present three ways to check the goodness of these fits: we investigate the goodness of each fit in all datasets, we define a combined goodness exploiting the logical structure of a simultaneous fit, and we stack the fit residuals of all datasets to detect weak features. These tools are applied to all RXTE-spectra from GRO 1008−57, revealing calibration features that are not detected significantly in any single spectrum. Stacking the residuals from the best-fit model for the Vela X-1 and XTE J1859+083 data evidences fluorescent emission lines that would have gone undetected otherwise.